Revelations - Sharratt, Mary, 1964- (Houghton Mifflin Harcourt, 2021)
"Bishop's Lynn, England, 1413. At the age of forty, Margery Kempe has nearly died giving birth to her fourteenth child. Fearing that another pregnancy might kill her, she makes a vow of celibacy, but she can't trust her husband to keep his end of the bargain. Desperate for counsel, she visits the famous anchoress Dame Julian of Norwich and confesses that she has been haunted by visceral religious visions. Julian offers up a confession of her own: she has written a secret, radical book about her own visions, Revelations of Divine Love. Nearing the end of her life and fearing Church authorities, Julian entrusts her precious book to Margery, who sets off the adventure of a lifetime to secretly spread Julian's words. -- adapted from jacket